The Effect of Pressure and Time Operation of Water Treatment of Gasing River on Pollutant Concentration by Using Ceramic Membrane Separation - Sisnayati Syechran (Sriwijaya Journal of Environment, 2018)
AbstractThe purpose of this study is  to treat water from Gasing River, Banyuasin District, South Sumatera Province by using ceramic membrane to produce clean water. Also, this study is to analyze the performance of ceramic membranes in terms of its ability to reduce the pollutants contained in water of Gasing River. The ceramic membrane was tube-shaped, made from clay (87.5% w), iron powder (2.5% w) and activated carbon of oil palm empty bunch (10% w). The operation condition of membrane separation was of 15 minutes; 30 minutes; 45 minutes; 60 minutes; 75 minutes; 90 minutes and the applied  pressure  was of 1.0 bar, 1.5 bar and 2.0 bar. The reduction pollutants (Fe, Mn, Zn, NH3-N, NO2- and PO4-3) concentration increased with increasing the pressure and the operating time of membrane separation, and the pollutants concentration in effluent was met the Environmental Quality Standards.